Readings on Argentinean Literature Tradition and Building of the Nation - González Sawczuk, Susana Inés (Pontificia Universidad Javeriana, 2014)
The following is a reflection on the importance of establishing a cultural heritage based on the setting of a literary tradition and the reading procedures carried out by the Argentinean writer, Ricardo Piglia (1940). An initial moment of genesis is highlighted in the construction of a tradition for a Nation.  They are works that serve as a framework for thinking out the basis of national literature. The lineage of Argentinean literature is defined in this journey that responds to reading procedures which discover the contexts that take possession of those narratives and dilemmas that are at stake, pointing to a logic that organizes and gives room to future incorporations.